Speed and power preparation of qualified water polo players - Ostrovs'kij, M. V.; Chaplins'kij, M. M.; Sidorko, O. J. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The scientific information of the improve of power and speed preparation of qualified water polo players were presented in the article. The application of power training exercises, similar in structure and composition with competitive acts of water polo players and also their purposeful use for developing power endurance, ultimate speed and explosive power, ensure their greatest development. It has been recognized determined that the use of speed training exercises in the middle of the training session is the most effective. In water polo training the practice of developing speed skills at the end of training session is the least effective. Combination of speed qualities training variants at different parts of training session throughout the year-round cycle of training adds the positive effect of speed qualification of water polo players in general.